STUDENTS’ EXPECTATIONS ON A TEACHER’S STRATEGIES IN CLASSROOM MANAGEMENT - Yuli Witarsa; Muhamad Taufik Hidayat (English Education and Applied Linguistics Journal (EEAL Journal), 2021)
The students’ expectations are very important since this often means assessing teachers or lectures after knowing the perception results of the students. The aims of the study is to identify what are students’ expectations on teacher’s strategies in classroom management. This research was carried out through qualitative method and a case study design. Two females students who have different achievements (middle up and middle low) used as participants of the study. Semi-structured interview was used in data collection. The techniques for data analysis were organize and prepare the data, read through the data, explore the data, analyze the data with the coding process, represent and report the findings, and interpret the meaning of the data. Two findings are obtained. First, intrinsic characteristics consisted of the teacher learning system for students, teacher shows mastery of the subject, teacher gives correction to the students, and the teacher’s attitude towards the students. Second, extrinsic characteristics consisted of the teacher to be on time for class, the teacher gives assigment to the students in classroom, the teacher manages students attendance in classroom, and the teacher language in classroom. As a result of this study, there are several different expectations between students middle up achiever and middle low achiever. The researcher believe that this information help other researcher conduct future research or develop their research to be more spesific.